Bacterial Photosensory Proteins and Their Role in Plant–pathogen Interactions1. (May 2017) - Kraiselburd, Ivana; Moyano, Laura; Carrau, Analía; Tano, Josefina; Orellano, Elena G.
Abstract: Light is an important environmental signal for almost all living organisms. The light perception is achieved by photoreceptor proteins. As can be observed from the great number of bacterial genomes sequenced, plant pathogenic bacteria encode for a large number of photoreceptor proteins. The physiological implications of these photoreceptors are still poorly characterized. However, recent studies revealed the participation of these photosensory proteins in the pathogenic process. Here, we summarize what is known about these proteins and their role during the virulence process, concluding that the light environment modulates the plant–pathogen interaction. Abstract : Light is an important source of energy and information, and it is perceived by photoreceptor proteins. The presence of these proteins in chemo‐heterotrophic bacteria has been identified. In plant pathogenic bacteria, different red and blue light photoreceptors were found including the following: phytochromes, LOV and BLUFs proteins. The photochemistry and functionality of these receptors were demonstrated in Pseudomonas spp., Agrobacterium tumefaciens and Xanthomonas spp. Furthermore, it was confirmed that they participate during the virulence process, modulating the aggressiveness symptoms allowing the bacterial multiplication and spreading and consequently a successful host infection.